A review of the concepts, terminologies and dilemmas in the assessment of decisional capacity: a focus on alcoholism. (December 2013) - Restifo, Sam
Objective: The formal assessment of a person's capacity for making reasoned decisions is an infrequent and usually unappealing clinical task. The purpose of this paper is to dissect the task, consider the component parts, clarify those aspects that can be problematic and highlight those that remain so. Method: The paper reviews the concepts, terminologies and dilemmas around alcoholism, insight, lack of insight, denial, judgement, will, decisional capacity and competence. Conclusion: Assessments of patients suffering from alcoholism (or any other dyscontrol problem such as deliberate self-harm, problem gambling or eating disorders) are likely to evoke unease because of the interweaving of potentially disputable phenomenological, clinical, ethical, semantic and legal aspects. Familiarity with the concepts and terms around decisional capacity helps to orientate clinicians in their work. There remain some particular conceptual issues that are in need of further scholarly attention.